2022
DOI: 10.3390/app122413043
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and Differences between Fat Estimation Formulas Using Kinanthropometry in a Physically Active Population

Abstract: The importance of fat mass estimation in multiple areas related to health and sports has led to the emergence of a large number of methods and formulas for its estimation. The aim of the present study was to compare the agreement and differences between different formulas for estimating fat mass by anthropometry. Eighty-seven subjects underwent an anthropometric assessment following the protocol from the International Society for the Advancement of Kinanthropometry (ISAK). The fat percentage was calculated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Fourthly, this research did not differentiate between the different types of athletics, given the size of the sample, but analyzed athletics as a whole. Fifth, although the equations for estimating body composition used in this research were chosen because they are recommended for growing populations [ 76 ], recent research has shown that the data reported by different body composition methods and equations differ from each other [ 77 ], so the data obtained for body composition in this research would have differed if other equations had been used [ 77 ]. Finally, the present investigation did not analyze the metabolic expenditure of the athletes, which could affect the anthropometric results of the athletes [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, this research did not differentiate between the different types of athletics, given the size of the sample, but analyzed athletics as a whole. Fifth, although the equations for estimating body composition used in this research were chosen because they are recommended for growing populations [ 76 ], recent research has shown that the data reported by different body composition methods and equations differ from each other [ 77 ], so the data obtained for body composition in this research would have differed if other equations had been used [ 77 ]. Finally, the present investigation did not analyze the metabolic expenditure of the athletes, which could affect the anthropometric results of the athletes [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…With an error (d) of 5.5 mm in the ∑8 skinfolds, the required sample was 165 subjects. Moreover, the calculation used to establish the required sample for each sex group was made using the ∑8 skinfolds standard deviation from research with samples of similar characteristics (SD = 27.35 for males; SD = 28.28 for females) [ 4 ]. With an error (d) of 6.0 mm in the ∑8 skinfolds in the case of the male population, and 6.2 mm in the case of the female population, the required sample was 79 subjects per group.…”
Section: Methodsmentioning
confidence: 99%
“…Among the different methods for assessing body composition, anthropometry is one of the most widely used for field testing to estimate body adiposity [ 1 , 2 ], as it is low-cost, portable technique, which uses relatively simple measurement procedures and allows for fast data collection. The measurement of skinfold thickness, which comprises two layers of skin and subcutaneous adipose tissue, allows both the estimation of adipose tissue, by usingthe value of individual skinfolds, considered an indirect method; and the estimation of lipid mass through the use of different regression equations, which includesskinfold values to estimate body density, and from body density estimate the lipid mass, so it is considered a doubly indirect method [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indirect methods use assumptions or algorithms to estimate a certain body composition component while double indirect methods use regression equations that have been validated from indirect methods, 22 with the exception of a few formulae that have been validated with cadaveric dissection. 23 Imaging methods such as magnetic resonance imaging or computerized axial tomography have been reported to have excellent accuracy in the measurement of SMM and those methods have also been validated with cadaveric dissection. 24 However, dual-energy X-ray absorptiometry (DXA) has recently emerged as an alternative method of providing a precise and reliable measurement of SMM.…”
Section: Introductionmentioning
confidence: 99%